Co-creation and application of a framework for the de-prioritization of urban communities during insecticide-treated bed net mass campaigns for malaria prevention and control in Kwara State, Nigeria - Ifeoma D. Ozodiegwu; Laurette Mhlanga; Eniola A. Bamgboye; Adeniyi F. Fagbamigbe; Cyril Ademu; Chukwu Okoronkwo; Joshua O. Akinyemi; Akintayo O. Ogunwale; IkeOluwapo O. Ajayi; Beatriz Galatas (BMC Global and Public Health)
Abstract Background Malaria continues to be a major cause of illness and death worldwide, particularly affecting children under the age of five and those living in high-burden countries like Nigeria. Long-lasting insecticidal nets (LLINs) are one of the effective interventions for malaria control and prevention. In response to funding constraints in the Global Fund Grant Cycle 7, Nigeria’s National Malaria Elimination Programme (NMEP) aimed to develop an approach that maximizes the impact of limited malaria interventions by focusing on areas with the greatest need. We developed an urban LLINs distribution framework and a novel strategy, which was piloted in Ilorin, the capital of Kwara State. Methods A participatory action research approach, combined with abductive inquiry, was employed to co-design a framework for guiding bed net distribution. The final framework consisted of three phases: planning, data review and co-decision-making, and implementation. During the framework’s operationalization, malaria risk scores were computed at the ward level using four key variables, including malaria case data and environmental factors, and subsequently mapped. A multistakeholder dialogue facilitated the selection of the final malaria risk maps. Additionally, data from an ongoing study were analyzed to determine whether local definitions of formal, informal, and slum settlements could inform community-level stratification of malaria risk in cities. Results Akanbi 4, a ward located in Ilorin South and Are 2, a ward in Ilorin East consistently had lower risk scores, a finding corroborated during the multistakeholder dialogue. A map combining malaria test positivity rates among children under five and the proportion of poor settlements was identified as the most accurate depiction of ward-level malaria risk. Malaria prevalence varied significantly across the categories of formal, informal, and slum settlements, resulting in specific definitions developed for Ilorin. Thirteen communities classified as formal settlements in Are 2 were de-prioritized during the bed net distribution campaign. Conclusions The framework shows promise in facilitating evidence-based decision-making under resource constraints. The findings highlight the importance of stakeholder engagement in evaluating data outputs, particularly in settings with limited and uncertain data. Enhancing surveillance systems is crucial for a more comprehensive approach to intervention tailoring, in alignment with WHO’s recommendations.